2020
DOI: 10.1016/j.jhazmat.2019.121788
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplastics: From tissue accumulation to cell translocation into Mytilus galloprovincialis hemocytes. resilience of immune cells exposed to nanoplastics and nanoplastics plus Vibrio splendidus combination

Abstract: Background Few studies have examined nano-sized plastic particulates (NPs) exposure in relation to oxidative stress and biochemical responses in rodents, commonly used for toxicity evaluations on which to base risk assessment for humans. Methods Here we explored possible oxidative stress and biochemical responses of ve weeks oral exposure to polystyrene (PS) nanoparticles (1, 3, 6 and 10 mg/kg body weight per day) in male rats. We used variance analysis and variance explained statistic eta-squared (2) to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 60 publications
7
77
0
3
Order By: Relevance
“…Efforts to quantify PS-NP within mussel tissues was unsuccessful, as we were unable to distinguish the red fluorescence signal of the particles from autofluorescence. However, we remain confident that uptake occurred given our observations of active feeding, and evidence from other research papers that PS-NP (either free-floating or aggregated with microalgae) can be filtered-out by mussels; in these studies, PS-NP uptake was ascertained by measuring reduction of nanoparticle concentrations in the surrounding water and/or visualising uptake of PS-NP within tissues via fluorescence imaging (Brandts et al, 2018a;Sendra et al, 2019;Wegner et al, 2012), although such imaging studies have been criticised as leaching of fluorophores may give false positives (Catarino et al, 2019). identified per mg of digestive gland tissue of individual mussels, following 24 h or 7-day exposure to 500 ng mL -1 microplastics.…”
Section: Microplastic and Nanoplastic Uptakementioning
confidence: 62%
“…Efforts to quantify PS-NP within mussel tissues was unsuccessful, as we were unable to distinguish the red fluorescence signal of the particles from autofluorescence. However, we remain confident that uptake occurred given our observations of active feeding, and evidence from other research papers that PS-NP (either free-floating or aggregated with microalgae) can be filtered-out by mussels; in these studies, PS-NP uptake was ascertained by measuring reduction of nanoparticle concentrations in the surrounding water and/or visualising uptake of PS-NP within tissues via fluorescence imaging (Brandts et al, 2018a;Sendra et al, 2019;Wegner et al, 2012), although such imaging studies have been criticised as leaching of fluorophores may give false positives (Catarino et al, 2019). identified per mg of digestive gland tissue of individual mussels, following 24 h or 7-day exposure to 500 ng mL -1 microplastics.…”
Section: Microplastic and Nanoplastic Uptakementioning
confidence: 62%
“…Furthermore, trophic transfer of plain PS NPs of different sizes (30, 100, and 500 nm) from mussels to the crab Carcinus maenas has been demonstrated under laboratory conditions (Farrell and Nelson, 2013). Some studies reported the ability of PS NPs to translocate from the hemolymph to target tissues in benthic invertebrates (Farrell and Nelson, 2013) in a size-dependent manner, with 50 nm of PS NPs more internalized by hemocytes than larger particles (Sendra et al, 2019a), taken up in immune cells, and cause oxidative stress, immunotoxicity, and genotoxicity (Canesi et al, 2015;Brandts et al, 2018;Bergami et al, 2019;Ciacci et al, 2019;Sendra et al, 2019a). In a recent study on the benthic foraminifer Ammonia parkinsoniana, plain PS NPs tested at a concentration of 1 µg ml −1 were internalized in the single-cell marine eukaryotes within 24 h, enhancing freeradical production and accumulation of intracellular neutral lipids (Ciacci et al, 2019).…”
Section: Effects On Marine Organismsmentioning
confidence: 99%
“…11 Moreover, PS-NPs have been previously found to interfere with the immune system of zebrafish 8,10,12 as well as other aquatic species. 13,14 In D. rerio, PS-NPs have been shown to upregulate the expression of inflammatory cytokines, 8 activate the complement system and oxidative stress mechanisms 10 and provoke DNA damage, induced by ROS and apoptosis. 11 In this context, we seek to address the question of whether their interaction with the immune system can affect the survival of populations in their natural environments, where organisms are frequently exposed to pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, barely any studies on the combination of PS-NPs and an immune challenge have been performed. In a recent study, Sendra et al 14 evaluated the response of Mytilus galloprovincialis haemocytes in vitro when infected with Vibrio splendidus, following an exposure to PS-NPs. They reported that the invertebrate's haemocytes showed resilience when infected with the bacteria, being able to recover their phagocytic capacity.…”
Section: Introductionmentioning
confidence: 99%